The Effect of Solvent Polarity and Extraction Time on the Antioxidant of Aquilaria malaccensis Leaves - Sumantri, Imam Bagus; Saragih, Awaluddin; Batubara, Ridwanti; Wahyuni, Henny Sri; Laila, Lia; Yuliasmi, Sri; Murni, Nelly; Baruna, Intan; Riati, Devi; Mustanti, Lolyta Fitri (Majalah Obat Tradisional, 2026)
Antioxidants have the capacity to donate electrons, thereby neutralizing free radicals responsible for oxidative damage linked to various disease. Aquilaria malaccensis possesses strong antioxidant potential and is a promising herbal source due to its polyphenolic compounds. However, antioxidant compounds such as polyphenols are unstable and require optimized extraction methods. This study aimed to examine the impact of solvent polarity and extraction time on the antioxidant properties of A. malaccensis leaves. The leaves were standardized, subjected to phytochemical screening, and extracted using ethanol:water mixtures with varying polarity ratios (96:0 to 0:100) at 60–70°C for 30 minutes. Extraction time was further varied from 30 to 120 minutes using water at 90–100°C. Each extract was assessed for its antioxidant activity, total phenolic content (TPC) and total flavonoid content (TFC). The results of phytochemical screening showed that the standardized leaves contained all secondary metabolite components. All extracts exhibited high antioxidant activity (IC50 values ranging from 14.82 to 84.57 µg/mL), TPC (60.75 to 280.15 mg GAE/g extract), and TFC (6.25 to 39.19 mg QE/ g extract). The highest antioxidant activity TPC, and TFC were obtained from extraction using ethanol: water (96:0) at 60-700C for 30 minutes. These findings suggest that solvent polarity and extraction time significantly influence the antioxidant capacity of A. malaccensis extracts.